2017
DOI: 10.1002/wsb.790
|View full text |Cite
|
Sign up to set email alerts
|

Performing statistical population reconstruction using Program PopRecon 2.0

Abstract: Statistical population reconstruction develops an integrated likelihood model that incorporates age‐at‐harvest composition, harvest totals, hunter effort, and auxiliary data on survival, harvest, or abundance to model demographics of harvested populations. Each statistical population reconstruction model is handcrafted to account for varying levels of available demographic data, hunting regulations, sampling of the harvest process, and biology of the harvested species. PopRecon 2.0 is a software program that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…We used tags sold as our measure of hunter effort primarily because it was the only data available for the majority of our study period, although some have suggested that measures such as hunter‐days might better represent hunter effort (Clawson et al ). A regression analysis indicated a surprisingly tight relationship between tags sold and hunter‐days.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We used tags sold as our measure of hunter effort primarily because it was the only data available for the majority of our study period, although some have suggested that measures such as hunter‐days might better represent hunter effort (Clawson et al ). A regression analysis indicated a surprisingly tight relationship between tags sold and hunter‐days.…”
Section: Discussionmentioning
confidence: 99%
“…If ages were generally underestimated, abundance estimates would also have been underestimated, and vice versa, although SPR analysis has been reported to be robust to errors in aging animals (Conn et al 2009). We used tags sold as our measure of hunter effort primarily because it was the only data available for the majority of our study period, although some have suggested that measures such as hunter-days might better represent hunter effort (Clawson et al 2017b). A regression analysis indicated a surprisingly tight relationship between tags sold and hunter-days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations